Comparison of Some Postural and Functional Factors in the Elderly With and Without a History of Falling - Kosar Esmaeili; Ebrahim Mohammad Ali Nasab Firouzjah; Morteza Homayounnia Firouzjah; Heather Hower (University of Tehran, 2024)
Introduction: Falling is one of the serious issues of old age that occurs due to many factors. This research aimed to compare static and dynamic balance, walking speed, spinal curvature, and central stability of elderly people with and without a history of falling.Methods: The current research was a causal-comparative research. 60 elderly women aged between 60 and 70 from Tabriz voluntarily participated in the research. The participants were assigned into two groups with and without a history of falling. The fall history of the participants was measured by the Fall Efficacy Scale. The static and dynamic balance were evaluated by Sharpened-Romberg and Timed Up and Go tests, respectively. Walking speed was measured with a 10-meter walk test, core stability was measured with McGill endurance tests, and spinal curvature was measured with a flexible ruler. Independent t-test was used to compare the mean variables in two groups.Results: The results showed a significant difference between the static and dynamic balance indices, lumbar spine curvature, walking speed, and core stability in the elderly with and without a history of falling. However, there was no significant difference between the curvature index of the lumbar spine in the elderly with and without a history of falling.Conclusion: According to the research results, it seems necessary to develop and improve the indices of balance, walking speed, and core stability in people with a history of falling.